2009
DOI: 10.1118/1.3152866
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo modeling of small photon fields: Quantifying the impact of focal spot size on source occlusion and output factors, and exploring miniphantom design for small‐field measurements

Abstract: The accuracy with which Monte Carlo models of photon beams generated by linear accelerators (linacs) can describe small-field dose distributions depends on the modeled width of the electron beam profile incident on the linac target. It is known that the electron focal spot width affects penumbra and cross-field profiles; here, the authors explore the extent to which source occlusion reduces linac output for smaller fields and larger spot sizes. A BEAMnrc Monte Carlo linac model has been used to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 31 publications
2
41
0
Order By: Relevance
“…A small but consistent change (1%–2%) in OF was observed, with the highest reading at 90°. This observation agreed with previous work of Scott et al (35) and Jaffray et al, (36) where a spot size slightly larger in the Y direction was reported.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A small but consistent change (1%–2%) in OF was observed, with the highest reading at 90°. This observation agreed with previous work of Scott et al (35) and Jaffray et al, (36) where a spot size slightly larger in the Y direction was reported.…”
Section: Discussionsupporting
confidence: 94%
“…Scott et al (35) demonstrated that Varian machines have a tilted elliptical shape source. At certain angles, an elongated jaw aperture result in higher OFs than at other angles.…”
Section: Discussionmentioning
confidence: 99%
“…The data (PDD, Profiles) are only different for extremely small fields and can be ignored for modern machines and within the accuracy needed. Scott et al (53) provided extensive data for the effect of source occlusion in small fields and its impact of profile and output. It was noted that effect is only pronounced for larger source size and very small fields (≥5 mm).…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of output factors for small photon fields to the diameter of the linear accelerator's initial electron beam has received increasing attention over recent years, with several authors recognising that the characteristics of small fields can be used for fine-scale optimisation of electron spot parameters used in Monte Carlo simulations of photon beams [1,2,3].…”
Section: Introductionmentioning
confidence: 99%
“…This study aims to demonstrate that the accuracy of the electron focal spot diameter used in a Monte Carlo model of a linear accelerator operating with or without an external microMLC can be 1 To whom any correspondence should be addressed. broadly verified with reference to narrow-beam dose profiles obtained from radiochromic film measurements.…”
Section: Introductionmentioning
confidence: 99%